Pengaruh Konsumsi Puding Bayam Merah terhadap Keluhan Dismenore dan Gejala Sindrom Premenstrual pada Remaja Putri: The Effect of Red Spinning Pudding Consumption on Complaints of Dymenorore and Premenstrual Syndrome Symptoms in Adolescent Women - Resmaniasih, Ketut (Jurnal Surya Medika (JSM), 2022)
Premenstrual syndrome (PMS) is a collection of symptoms caused by hormonal changes that last about two weeks before menstruation until the start. In addition to hormonal changes (an increased estrogen hormone), several other contributing factors include vitamin and mineral deficiencies such as vitamin B, calcium, magnesium, lack of physical activity, and stress. This study aimed to find out more clearly the effect of consuming red spinach pudding on complaints of dysmenorrhea and symptoms of premenstrual syndrome in adolescent girls. This study used a Quasy Experiment with a two-group pretest-posttest design with a total sample of 60 people. Based on the linear regression analysis results after controlling for the confounding variables BMI and HB levels, the mean reduction in PMS scores in the intervention group was 2.44 and in the control group was 0.54. The mean difference between groups was 2.98, with a p-value = 0.009. The results showed a decrease in the mean premenstrual syndrome score in the group of young women who consumed red spinach pudding.